Bioefficacy of some indigenous plant extracts against epilachna beetle (Henosepilachn (The Journal of Plant Protection Sciences, 2020)
A field trial was conducted on ‘Barapata’ variety of cucumber in a replicated Randomized Block Design at Viswavidyalaya Instructional Farm during 2004–05 to find out the impact of plant derived pesticides viz; Neem Azal, Rhizome extracts of Acorus calamus with petroleum ether as solvent and seed extracts of Annona squamosa with methanol as solvent in controlling epilachna beetle,Henosepilachna vigintioctopunctata, Fabr; Both Neem Azal and seed extracts of Annona squamosa were used at 4ml, 5ml and 6ml (per Lt. of water) while this was 1ml, 2ml and 3ml (per Lt. of water)in case of petroleum ether extract of rhizome of Acorus calamus. Endosulfan 35 EC was used at 1ml,1.5ml and 2ml (per Lt. of water) to compare the efficacy of plant products. Results of the experiment revealed that Endosulfan 35 EC at 2mL-1 of water performed very well in reducing population buildup of Henosepilachna vigintioctopunctata, Fabr. to the extent of 75.00%, while among the botanical  revealed that Endosulfan 35 EC at 2mL-1 of water performed very well in reducing population build up of Henosepilachna vigintioctopunctata, Fabr. to the extent of 75.00%, while among the botanical Acorus calamus at 2mL-1 of water.
Keywords: Plant extracts bioefficacy; Epilachna beetle; Cucumber